Determination of Load Carrying Capacity of Clay Bricks Reinforced With Straw - Odeyemi, Samson Olalekan; Akinpelu, Mutiu Adelodun; Atoyebi, Olumoyewa Dotun; Yahaya, Rukayah Titilope (International Journal of Sustainable Construction Engineering and Technology, 2017)
Sandcrete block is a dominant material for wall construction but it is often characterized with high cost and low strength property. This has necessitated the need to source for new materials within our environment. Clay is a natural material that is widely available in many countries of the world and it has the potential to establish better strength property than sandcrete blocks when mixed with straw. The straw serves as reinforcement that increases its compressive strength. The results obtained from this research shows that with the addition of straw (0.0025%, 0.005%, 0.0075% and 0.01%) at water-clay mixing ratio of 0.15, the compressive strength of the clay brick increased up to 148% of the strength of the clay without straw. The Scanning Electron Micrograph (SEM) results shows a strong adhesion between brick and straw fiber without any sign of brick saturation. This reveals that the addition of straw increased the compressive strength of the clay brick.